2022-RA-1084-ESGO Oncological outcomes in patients having neoadjuvant chemotherapy who do not undergo intended interval debulking surgery. (20th October 2022) - Yao, Si Liang; Simpkins, Megan; Rider, Liadin; Cao, Jiexin; Underwood, Camilla; Tryczynska, Monica; Ajakaiye, Anuoluwa; Vergeldt, Tineke; Jones, Rachel; Hanna, Louise; Lim, Kenneth; Sharma, Aarti; et al.
Abstract : Introduction/Background: A common treatment approach for patients with FIGO stage III/IV ovarian cancer is neoadjuvant chemotherapy (NACT) with interval debulking surgery (IDS) with subsequent adjuvant chemotherapy. However, not all patients undergo the intended surgery for multiple reasons. Outcome data for these patients is limited, however, reduced survival has been reported in literature. This study aimed to assess and compare the oncological outcomes of patients who did not undergo IDS following NACT for stage III/IV ovarian cancer in Wales. Methodology: The Wales Cancer Network identified all patients with stage III/IV ovarian cancer scheduled for NACT across the three Cancer centres in Wales in 2018 and 2019. The Welsh Clinical Portal and CANISC were used to gather data on patients' demographics, disease stage, treatment plans, complications, reasons for not having surgery, and oncological outcomes. Results: 197 patients were included, of which 128 (65%) underwent surgery and 69 (35%) did not. Across Wales, the patients who had surgery were on average younger (64.2 vs 70.8 years), had fewer comorbidities (average 2.7 vs 3.0), a better performance status at diagnosis (average 0.8 vs 1.5), but had the same average BMI (28.9) compared to those who did not. The majority of patients who underwent surgery had zero complications (58.6%). Across Wales, 99.13%, 93.91%, 74.78%, and 58.26% of patients who underwent IDS survived at 6, 12, 24, and 36 months respectively, compared to 90.00%, 73.33%, 40.00%, and 20.00% who did not (p=0.0034, 0.0001, 0.0001, 0.0001 respectively). Conclusion: Across Wales, 35% of women with stage III/IV ovarian cancer did not undergo their intended surgery after NACT. In this retrospective cohort, the survival was lower in those who did not have surgery. Common reasons for not proceeding with surgery included disease progression, fitness for surgery, and patient choice.